Room‐Temperature Photoconductivity Far Below the Semiconductor Bandgap. (1st September 2014) - Huang, Zhiming; Tong, Jinchao; Huang, Jingguo; Zhou, Wei; Wu, Jing; Gao, Yanqing; Lu, Jinxing; Lin, Tie; Wei, Yanfeng; Chu, Junhao
<x xml:space="preserve">Abstract</x> A concept to stimulate photoconductivity in a semiconductor well below its bandgap in a metal–semiconductor–metal structure with sub‐wavelength spacing is proposed. A potential well is induced in the semiconductor by external electromagnetic radiation to trap carriers from the metals. This opens an avenue to generate carriers by photons without adequate excitation energy and is expected to have great significance in modern materials. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>